The influence of the usage of the male condom by seniors in the vulnerability to HIV: a systematic review with meta-analysis - Paz, Marcella Alves da; Alencar, João Márcio Nunes de; Sousa, Cláudia Layse Almeida; Anjos, Ulisses Umbelino dos; Nogueira, Jordana de Almeida; Rodrigues, Jailson Alberto (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Brazil has presented a rise of the population aged over 60 years. In addition to this change in demographic profile, there is an epidemic of worldwide, HIV infection. Objective: Was to ascertain the influence of the use of male condoms by seniors in vulnerability to virus infection. Methods: We developed a systematic literature review and meta-analysis of observational studies, research being conducted in the following databases: SciELO, LILACS, electronic library at UFMG and USP and Google Scholar. Results: A number of 38 articles were selected and after evaluation and application of the Physiotherapy Evidence Database (PEDro) scale, 6 of them were elected to compose the study sample. The statistical analysis obtained a summary measure (odds ratio − OR=1.643). Conclusion: From the analysis of the database, one realizes that the indicator found (summary measure), the condom use is ratified as a factor or protection against HIV infection, in other words, its adoption makes the individual less vulnerable.